COMPETENCY ICT IN INITIAL TEACHER TRAINING:DESCRIPTIVE STUDY FOR DECISION-MAKING IN THE CURRICULUM. - Pedro Sandoval Rubilar; Francisco Rodriguez Alveal; Ana Maldonado Fuentes (Editora da Universidade de Santa Cruz do Sul, 2011)
The article shows the results of a research study, which was carried out in a regional public state university from southern Chile, in order to find out knowledge and use of ICT that Initial Teacher Training Program students have. Specifically, the study intends to look for answers related to computer literacy, type of access and use of ICT and, at the same time, promotes reflection on how the curriculum should prepare future teachers in order to guarantee learning and competencies in this area. Using a transversal descriptive quantitative methodology, a validated questionnaire (Cronbach Alpha 0.89) was answered by a sample of 150 students belonging to cohort 2009. We conclude that teacher training students have an easy access to ICT resources and, therefore, they are native subjects who show a high computer literacy degree. However, they do not use specific programs related to education nor do they know how they can take advantage of that ICT knowledge in the teaching learning process within the classroom in their future professional career.